Analisis Tingkat Kepuasan Pasien Terhadap Layanan Kesehatan Klinik Del - Theo Hosea M; Mariana Simanjuntak (UNIVERSITAS SERAMBI MEKKAH, 2024)
This study analyzes patient satisfaction levels with healthcare services at Klinik Del within the context of a highly competitive industry. Through a survey using a Likert scale of 1-10, various aspects such as service quality, waiting time, facility availability, communication with medical staff, and cost were evaluated. The study found that customer reviews and ratings have a positive and significant impact on purchase decisions, demonstrated by strong loading factor values. The research instruments showed outer loadings above 0.70, except for a few indicators that need improvement. These findings provide valuable insights for Klinik Del to enhance their services and also benefit the healthcare industry in understanding patient needs and expectations, enabling the adaptation of best practices to improve overall healthcare standards.